Analytical approach for time‐dependent groundwater inflow into shield tunnel face in confined aquifer. (1st December 2017) - Liu, Xiao‐Xue; Shen, Shui‐Long; Xu, Ye‐Shuang; Yin, Zhen‐Yu
Summary: Prediction of time‐dependent groundwater inflow into a shield tunnel is a significant task facing engineers. Published literature shows that there is no available method with which to predict time‐dependent groundwater inflow into a tunnel. This paper presents a prediction approach for time‐dependent groundwater inflow into a tunnel in both anisotropic and isotropic confined aquifers. The proposed solution can predict groundwater inrush from the tunnel cutting face. To obtain the time‐dependent groundwater flow quantity, the concept of a horizontal‐well pumping test based on the theory of a point source is adopted. Multiple factors, eg, drawdown, thickness of aquifer, conductivities, and specific storage, are taken into account. Both groundwater inflow to the cross section of a tunnel face in the y ‐ z plane and total tunnel inflow are obtained. Based on the proposed approach, the time‐dependent groundwater inflow to a tunnel can be classified as either a uniform or non‐uniform flow. The proposed approach is applied to analyse groundwater inflow of 2 field cases: (1) Metro line No. 7, Guangzhou City and (2) an underground tunnel in Huizhou, Guangdong Province. Results show that the proposed method can predict the measured values, and drawdown‐related curves are also derived. In addition, the calculated results also reveal that the effect of hydraulic conductivity k z on the total groundwater inflow differs from that of hydraulic conductivities k x and k y and the thickness of the aquifer.